Colonization of Mouse Spermatogonial Cells in Modified Soft Agar Culture System Utilizing Nanofibrous Scaffold: A New Approach: - Talebi, Ali; Sadighi Gilani, Mohammad Ali; Koruji, Morteza; Ai, Jafar; Rezaie, Mohammad Jafar; Salehi, Majid; Navid, Shadan; Abbasi, Mehdi (Galen Medical Journal, 2019)
Background: Spermatogonial stem cells (SSCs) are considered in fertility management approaches of prepubertal boys facing cancer therapies. However, in vitro propagation has become an important issue due to a small number of SSCs in testicular tissue. The present study aimed to investigate a modified soft agar culture system by using a nanofibrous scaffold as a new approach to mimic in vivo conditions of SSCs development. Materials and Methods: The SSCs were isolated from neonate mouse testes, cultured on polycaprolactone scaffold, and covered by a layer of soft agar for 2 weeks. Then, the number and diameter of colonies formed in experimental groups were measured and spermatogonial markers (i.e., Plzf, GfrÎ±1, Id4, and c-Kit) in SSCs colonies were evaluated by a real-time polymerase chain reaction and immunostaining. Results: Our results indicated that the colonization rate of SSCs was significantly higher in the present modified soft agar culture system (P<0.05). Only Plzf indicated a significant increased at the levels (P<0.05), the gene expression levels of Id4, Plzf, and GfrÎ±1 were higher in the present culture system. In addition, the expression of the c-Kit gene as a differentiating spermatogonia marker was higher in presence of scaffold and soft agar compared with the amount of other experimental groups (P<0.05). Conclusion: The culture system by using nanofibrous scaffold and soft agar as a new culture method suggests the potential of this approach in SSCs enrichment and differentiation strategies for male infertility treatments, as well as in vitro spermatogenesis. [GMJ.2019;8:e1319]